2011
DOI: 10.1080/14780887.2011.575288
|View full text |Cite
|
Sign up to set email alerts
|

A Disquisition on Pluralism in Qualitative Methods: The Troublesome Case of a Critical Narrative Analysis

Abstract: This article uses a research example as a case study of qualitative pluralism in practice to analyse issues involved. The case was a critical narrative analysis of interview data about clinical psychologists ' Personal and Professional Development (PPD). The rationale for a pluralist methodology to address critical research questions is described. To examine participants' PPD in terms of the relationship between individual subjectivities, group identities and societal power relations, elements of IPA, Grounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In line with the suggestion of Murray ( 37 ) 3 and other authors, we distinguished between the personal, interpersonal and ideological level of context in our analysis. Because most of the common methods in qualitative research do not cross the “categorical binary of individual and society” [( 46 ), 190] we needed to combine several methods of analysis for this purpose. The analytical framework that is presented in Table 2 is the result of a dynamic and abductive process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the suggestion of Murray ( 37 ) 3 and other authors, we distinguished between the personal, interpersonal and ideological level of context in our analysis. Because most of the common methods in qualitative research do not cross the “categorical binary of individual and society” [( 46 ), 190] we needed to combine several methods of analysis for this purpose. The analytical framework that is presented in Table 2 is the result of a dynamic and abductive process.…”
Section: Methodsmentioning
confidence: 99%
“…Reviewing narrative studies on mental health recovery, Spector-Mersel and Knaifel ( 13 ) identified that the holistic principle was often disregarded in the process of data-analysis. Other scholars have observed that researchers often neglect the socio-cultural context of narratives ( 35 ), or exclusively focus on either the personal or social dimensions of the telling ( 37 , 46 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using a pragmatic, pluralistic methodology in qualitative research can ameliorate some of the tensions and limitations inherent within the pure methodologies (Maggs-Rapport, 2000;Morse and Chung, 2003). Goodbody and Burns (2011) noted the challenges they faced in finding a methodology that was consistent with the aims of their research, whilst discussed how a pragmatic approach addressed some of these issues by allowing them to utilise a combination of different positions. Indeed, it was suggested that within pragmatism a clash between ontology and epistemology was negated by their alignment with the aims of the research (Chamberlain, Cain, Sheridan, and Dupuis, 2011).…”
Section: Pragmatism As a Methodological Approachmentioning
confidence: 99%
“…‘Casts’ (Savin‐Baden and Howell Major, ) or overtones from a range of different methodologies were drawn on for this research. Goodbody and Burns () noted the challenges they faced in finding a methodology that was ‘epistemologically and ontologically consistent’ with the aims of their research, whilst Frost and Nolas () discussed how a pragmatic approach addressed some of these issues by allowing them to utilise a ‘combination of ontological positions’. Under a pragmatic research umbrella it is possible to combine several different approaches and methodologies (Caelli, Ray and Mill, ) and this pluralist perspective was able to limit some of the issues concomitant with discrete methodologies (Onwuegbuzie and Leech, ).…”
Section: Research Projectmentioning
confidence: 99%